The Values Of Saprahan As A Resolution Of Sara Conflict In Pontianak Malay Society In The Perspective Of Islamic Law - I Nyoman Budi Artawan; Darussalam Syamsuddin; Abdul Wahid Haddade; Zarul Arifin (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2025)
The tradition of Saprahan is one of the local wisdoms of the Pontianak Malay community, rich in social, cultural, and spiritual values in community life. In the context of a diverse society and the potential for ethnic, religious, racial, and intergroup conflicts, this tradition has a strategic function as a means of conflict resolution based on custom that is in harmony with the principles of Islamic law. This study aims to analyze how the values of Saprahan are applied as a method of conflict resolution in the Pontianak Malay community and the extent to which these values reflect the principles of justice and peace in Islamic law. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews with traditional leaders, religious leaders, academics, and government officials, as well as documentation and participatory observation of Saprahan practices. Data analysis was conducted using reduction, categorization, and inductive reasoning techniques. The results of the study indicate that Saprahan not only serves as a traditional custom but also as an effective social institution for resolving conflicts without resorting to formal legal channels. The resolution process, which is based on deliberation, equality, and kinship, makes Saprahan a concrete manifestation of the principles of justice and peace in Islam. The harmony between local cultural values and Islamic law contributes significantly to maintaining social harmony and preventing conflict escalation in a multicultural society.